APPLICATION OF CRIMINAL LAW TO UTILIZATION ARTIFICIAL INTELLIGENCEIN INDONESIA - Murshal Senjaya, (International Journal of Social Science, 2023)
In Indonesia there are no specific legal regulations that regulate AI, this is the reason the ITE Law has an expansion to regulate legal regulations related to AI. In the ITE Law, AI is an electronic system and electronic agent where the elements contained in the legal regulation of electronic systems and electronic agents in this case are in accordance with the characteristics of AI in carrying out the actions and deeds it carries out. In relation to actions carried out by AI, those who have the authority to be responsible under the ITE Law are electronic system administrators who consist of legal subjects who can be held accountable for the use of AI. The use of AI from a criminal law perspective, in this case, AI cannot be classified as a legal subject, because according to several experts, the concept of responsibility is that it has awareness and can will its actions, and as is known, AI does not have awareness of the actions it carries out and also AI cannot will it. regarding the possibility of a criminal act being committed, and from a criminal law perspective related to responsibility in the use of AI, the creators and users of AI can be held responsible for the actions committed by the AI. Because humans are absolute legal subjects in criminal law who have awareness and an element of intentionality regarding the actions and actions carried out by AI